MOTIVASI DAN RESPON SISWA DALAM BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PROJECK BASED LEARNING (PjBL) - Sriyanti, Ika; Otisia Arinindyah; Isep Budiman; Endang Komara; Rita Sulastini; Okke Rosmaladewi (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2024)
ABSTRACT To improve students' motivation and response in learning mathematics, teachers must use a learning model that requires students to be active in learning activities or known as (student center). One model that requires students to be active is project-based or Project Based Learning (PjBL). This study aims to determine the motivation and response of students in Project Based Learning (PjBL). The method used in this study is a qualitative method of the Ethnography type. The instrument used in this study is a questionnaire or questionnaire, namely a questionnaire containing statements about Motivation and Response statements. The sample taken based on Simple Random Sampling, which was taken randomly with two different classes, namely class XA and XD. The approach in this study is Qualitative Ethnography research, the instrument used in this study is a questionnaire or questionnaire. The questionnaire was made differently to determine the motivation and response of students in Project Based Learning (PjBL). Data analysis used a Likert scale consisting of five answer choices, namely Strongly Disagree (STS), Disagree (TS), Neutral (N), Agree (S), and Strongly Agree (SS). Based on the results of the average Likert scale of student responses to mathematics lessons is 3.86, student responses to the Project Based Learning (PjBL) learning model are 3.40, and student responses to mathematics problems are 3.16. This shows that students give positive responses to all indicators. While the average results of the Likert scale of student motivation that shows interest in mathematics learning is 4.06, student learning motivation towards the Project Based Learning (PjBL) learning model is 4.16. This shows that students give positive motivation to all indicators. Keywords: Motivation, Response, Project Based Learning (PjBL